Pengaruh Pemasangan Bluff Body Terhadap Karakteristik Pembakaran Biobriket - Adhes Gamayel (Universitas Muhammadiyah Yogyakarta, 2014)
Biofuels are organic feedstock fuel produced by living organisms, such as solids, liquids, or gases. Biobriket combustion process is affected by the heating value biobriket constituent materials and the amount of air entering the biobriket combustion chamber. The purpose of this study isto determine the effect of variations of the bluff bodygeometry on the biobriket burning process. The independent variable used in this study, arethe fan rotation and the bluff bodygeometry. Fan rotation being used are 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm and 2000 rpm, while the bluff body geometry are round, triangle, square, hexagon and octagon. Triangular cross-section bluff body was noted to produce the highest temperature of 33.21 °C at 100 second. While the lowest temperature wasreached at 500 second with 31.18 oC. Fan rotation at 2000 rpm was found to produce the most rapid combustion,burnt out 10 grams of biobriket within 500 seconds.The conclusion to this study is the higher the fan rotation speed, the faster the combustion process of the biobriket. Triangular bluff body was found the best shape in this study.